Pemahaman Akuntansi, Sistem Pengendalian Intern, Sumber Daya Manusia, Komitmen Organisasi, dan Kualitas Laporan Keuangan - Artiwi, Putri; Kresnandra, Anak Agung Ngurah Agung (E-Jurnal Akuntansi; Vol 33 No 11 (2023)DO - 10.24843/EJA.2023.v33.i11.p14, 2023)
This research aims to determine the influence of understanding accounting, internal control systems, human resources, and organizational commitment on the quality of the Buleleng Regency Regional Apparatus Organization (OPD) financial reports. The sampling method used was purposive sampling and the sample size was 93 respondents. This research uses classical assumption test research techniques, multiple linear regression analysis, and the F test. The results of this research show that understanding accounting, internal control systems, and human resources have a positive effect, while organizational commitment has no effect on the quality of local government financial reports in Buleleng Regency. This research can provide additional empirical study information regarding the influence of understanding accounting, internal control systems, human resources, and organizational commitment on the quality of Buleleng Regency OPD financial reports, providing contributions and implications for Buleleng Regency OPD and providing a broader understanding for researchers and reader. Keywords: Understanding of Accounting; Internal Control Systems; Human Resources; Organizational Commitment; Quality of Financial Reports